THE INTEGRATION OF TECHNOLOGY AND INTERDISCIPLINARY COLLABORATION IN HEALTHCARE SETTINGS TO IMPROVE PATIENT CARE OUTCOMES AND OPTIMIZE OPERATIONAL EFFICIENCY - Hani Mohammed Ali Alhejji; Dalal Mohammed Ali Alaithan; Murtadha Mohsin Almuallem; Alsaleem, Fatimah Hassan M; Wala Ahmed Al Nasser; Essa Yassen Alsheikh; Ali saud Altalalwah; Ali yousef Almoqhawi; Zaki Hussain Bu Shehab; Al Ibrahim Hassan Baqqer M; Lutf Allh, Amnah Ahmed A; Zainab Yousef Al Burayh; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
In recent years, the healthcare industry has witnessed a significant transformation driven by the integration of technology and interdisciplinary collaboration. This review article explores the impact of leveraging technology and fostering interdisciplinary collaboration in healthcare settings to enhance patient care outcomes and streamline operational efficiency. The integration of technological advancements such as electronic health records, telemedicine, wearable devices, and artificial intelligence has revolutionized the way healthcare providers deliver care and interact with patients. Furthermore, interdisciplinary collaboration among healthcare professionals from various specialties has proven to be crucial in addressing complex patient needs and ensuring comprehensive care delivery.This review synthesizes existing literature on the benefits and challenges associated with the integration of technology and interdisciplinary collaboration in healthcare settings. It highlights the positive outcomes of adopting a multidisciplinary approach, including improved patient outcomes, enhanced care coordination, and increased operational efficiency. Moreover, the review discusses the potential barriers to successful implementation, such as data security concerns, interoperability issues, and resistance to change among healthcare professionals.